2021
DOI: 10.1080/14786419.2021.1925894
|View full text |Cite
|
Sign up to set email alerts
|

Computational and experimental insights on the interaction of artemisinin, dihydroartemisinin and chloroquine with SARS-CoV-2 spike protein receptor-binding domain (RBD)

Abstract: The mechanism of host cell invasion of severe acute respiratory syndrome coronavirus-2 SARS-CoV-2 is connected with the interaction of spike protein (S) with angiotensin-converting enzyme 2 (ACE2) through receptor-binding domain (RBD). Small molecules targeting this assembly are being investigated as drug candidates to contrast SARS-CoV-2. In this context, chloroquine, an antimalarial agent proposed as a repurposed drug to treat coronavirus disease-19 (COVID-19), was hypothesized to bind RBD among its other me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Artemisinins including artesunate and the newer amino-artemisinins, artemiside and artemisone [28], are prepared by synthetic modification of the parent drug, artemisinin, obtained from the sweet wormwood Artemisia annua that has been used in Chinese traditional medicine for treating fevers. Artemisinins are shown to reduce the production of SARS-CoV-2 proteins, block infection at post entry level and interfere with the RBD [22,29]. More recently, artesunate has been selected for a Phase III study in COVID-19 patients, essentially based on its anti-inflammatory, rather than virucidal, properties (WHO Solidarity Trial, https://www.isrctn.com/ISRCTN18066414, accessed on 15 September 2021).…”
Section: Antimalarial Compounds Against Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…Artemisinins including artesunate and the newer amino-artemisinins, artemiside and artemisone [28], are prepared by synthetic modification of the parent drug, artemisinin, obtained from the sweet wormwood Artemisia annua that has been used in Chinese traditional medicine for treating fevers. Artemisinins are shown to reduce the production of SARS-CoV-2 proteins, block infection at post entry level and interfere with the RBD [22,29]. More recently, artesunate has been selected for a Phase III study in COVID-19 patients, essentially based on its anti-inflammatory, rather than virucidal, properties (WHO Solidarity Trial, https://www.isrctn.com/ISRCTN18066414, accessed on 15 September 2021).…”
Section: Antimalarial Compounds Against Sars-cov-2mentioning
confidence: 99%
“…Antimalarial drugs were among the first to be selected for repurposing as drugs against SARS-CoV-2 [20], for which different mechanisms, such as the inhibition of endocytic pathways by elevation of endosomal pH and the interference of ACE2 with glycosylation have been proposed [21]. In this respect, activities of chloroquine and other antimalarial drugs such as artemisinins have been reported [22][23][24], although the efficacy of chloroquine is debatable [25]. In the current study, the interaction of natural and synthetic compounds with antimalarial activity with the RBD and ACE2 are examined.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the use of renin inhibitors, ACEIs and ARBs, and angiotensin (1-7) analogs may help regulate the RAAS pathway by increasing the angiotensin (1-7) levels (Gurwitz 2020;Offringa et al 2020). Inhibition and blockage of virus-ACE2 interaction utilizing antiviral peptides or peptides mimicking human ACE2 using computational modeling studies can offer potential use in prophylactic or therapeutic tools to fight against COVID-19 (Vaduganathan et al 2020;Karoyan et al 2021;Rathod et al 2020;Yang et al 2020;Sakkiah et al 2021;Han and Král 2020).…”
Section: Molecular Docking Of Ligands Into the Sars-cov-2 Spike Protein And Ace2 Complexmentioning
confidence: 99%
“…Molecular dynamics simulation performed on the crystal structure of the SARS-CoV2 RBD bound to ACE2 (PDB code: 6M0J) demonstrated that the maximum number of hydrogen bonds was observed between the receptor binding motif of the spike and the residues located at 35-54 and 325-331 from ACE2 binding domain (Jafary et al 2021). In silico computational approaches have been utilized in this regard as the first step to screen potential inhibitors such as small organic molecules, natural products, peptide mimics or miniproteins to block spike-ACE2 intermolecular interactions (Prashantha et al 2021;Ribaudo et al 2021;Schütz et al 2020). Published PDB crystal structures were then extensively used by previous investigators to study and analyze spike S-glycoprotein and ACE2 receptor interactions (Day et al 2021;Akachar et al 2020).…”
Section: Binding Affinity Scoresmentioning
confidence: 99%
“…However, molecular docking studies indicate that artemisinins may also bind to coronavirus-host proteins such as E protein, helicase protein, N protein, 3CL PRO , S protein, nonstructural protein 3 (nsp3), nsp10, nsp14, nsp15, cathepsin-L, and glucose-regulated protein 78 receptor ( Fuzimoto, 2021 ; Ribaudo et al, 2021 ) and part of the biological activity of artemisinin against COVID-19 may thus also be partially based on inhibiting the function of these viral proteins.…”
Section: Artemisinins: Potentials In Combating Covid-19 and Other Hum...mentioning
confidence: 99%